Regional brain volume differences in symptomatic and presymptomatic carriers of familial Alzheimer's disease mutations. Issue 2 (20th October 2012) - Lee, Grace J; Lu, Po H; Medina, Luis D; Rodriguez-Agudelo, Yaneth; Melchor, Stephanie; Coppola, Giovanni; Braskie, Meredith N; Hua, Xue; Apostolova, Liana G; Leow, Alex D; Thompson, Paul M; Ringman, John M
Abstract : Background: Mutations in the presenilin ( PSEN1, PSEN2 ) and amyloid precursor protein ( APP ) genes cause familial Alzheimer's disease (FAD) in a nearly fully penetrant, autosomal dominant manner, providing a unique opportunity to study presymptomatic individuals who can be predicted to develop Alzheimer's disease (AD) with essentially 100% certainty. Using tensor-based morphometry (TBM), we examined brain volume differences between presymptomatic and symptomatic FAD mutation carriers and non-carrier (NC) relatives. Methods: Twenty-five mutation carriers and 10 NC relatives underwent brain MRI and clinical assessment. Four mutation carriers had dementia (MUT-Dem), 12 had amnestic mild cognitive impairment (MUT-aMCI) and nine were cognitively normal (MUT-Norm). TBM brain volume maps of MUT-Norm, MUT-aMCI and MUT-Dem subjects were compared to NC subjects. Results: MUT-Norm subjects exhibited significantly smaller volumes in the thalamus, caudate and putamen. MUT-aMCI subjects had smaller volumes in the thalamus, splenium and pons, but not in the caudate or putamen. MUT-Dem subjects demonstrated smaller volumes in temporal, parietal and left frontal regions. As non-demented carriers approached the expected age of dementia diagnosis, this was associated with larger ventricular and caudate volumes and a trend towards smaller temporal lobe volume. Conclusions: Cognitively intact FAD mutation carriers had lower thalamic, caudate and putamen volumes, and we found preliminary evidence for increasing caudate size during the predementia stage. These regions may be affected earliest during prodromal stages of FAD, while cortical atrophy may occur in later stages, when carriers show cognitive deficits. Further studies of this population will help us understand the progression of neurobiological changes in AD.